Pengaruh Pengendalian Internal Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan SPBU Surakarta - Winiawati, Marlia; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
The employees performance in the company is one of the factors that are expected to support the achievement of corporate objectives. Employee performance is influenced by several factors, one of which is internal control as it is fundamental in governance to ensure governance objectives achieved effectively and efficiently. In addition, an ideal leader must have good leadership style, so it can improve the performance of employees. The purpose of this research is to determine the effect of internal control and leadership style on employees performance of gas station of Surakarta. Research samples are 124 gas station employees by purposive sampling method. Data analysis in this study are multiple linear regression. The results showed that internal control and leadership style effecting on employees performance.